Inhibition of neuronal nitric oxide synthase expression and prevention of mitochondrial dysfunction at spinal ventral horn after c7 spinal root avulsion in rats with taxol - Sze Kiat, Sim (2014)

(untitled)
Introduction Functional outcome following surgical repair in brachial plexus avulsion injury remains poor. Spinal motorneuron death after brachial plexus avulsion injury has been identified as the neurobiological barrier to functional restitution. Post injury oxidative stress reaction, for example, up-regulation of neuronal nitric oxide synthase (nNOS), not only cause direct damage to the motoneurons, but lead to mitochondrial dysfunction as well, especially the cytochrome c oxidase (CcO) activity, which serve as the main energy generator for neuronal normal activities. Furthermore, the impaired retrograde axonal transport of neurotrophic factors (which are vital for motoneurons survival) secondary to neurofibrogenesis and mitochondrial dysfunction has retarded the neuronal regeneration process. Taxol, a diterpene alkaloid, has the effect in slowing the neurofibrogenesis by microtubule stabilization and facilitate axonal regeneration in rats. This study was designed to evaluate the neuroprotective effect of intrathecally infused Taxol in the prevention of motoneuron death and mitochondrial dysfunction following brachial plexus avulsion injury. Material and Method Sprague-Dawley rats were divided into Treatment and Control groups (each group N=32). Brachial root avulsion injury was induced in each rat. The Treatment group received 5 days intrathecal infusion of Taxol (256ng/day) via a micro infusion pump, whereas the Control group received normal saline. Cervical cord was harvested at survival interval of 1 week, 2 weeks, 4 weeks and 6 weeks (n=8 in each subgroup). Number of surviving motoneurons and nNOS-positive motoneurons at injuredventral horn were determined with NADPH-d histochemistry with neutral red counterstaining. Mitochondrial function at the injured ventral horn was measured with CcO histochemistry and densitometer. Independent t-test was applied to detect differences between the study groups at specific survival interval. Results Compared to Control group, the Taxol treated group showed significant reduction in the nNOS expression at 2 weeks, 4 weeks, and 6 weeks, and significantly improved mitochondrial functions at 4 weeks and 6 weeks. The motoneurons survival rate was significantly increased at 2 weeks, 4 weeks, and 6 weeks in Taxol treated rats. Conclusions Taxol has the neuroprotective effect to prevent spinal motoneuron degenaration following brachial plexus avulsion injury by inhibiting nNOS expression and preventing mitochondrial dysfunction.